3(x+8)=6(x+5)+1

Simple and best practice solution for 3(x+8)=6(x+5)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+8)=6(x+5)+1 equation:



3(x+8)=6(x+5)+1
We move all terms to the left:
3(x+8)-(6(x+5)+1)=0
We multiply parentheses
3x-(6(x+5)+1)+24=0
We calculate terms in parentheses: -(6(x+5)+1), so:
6(x+5)+1
We multiply parentheses
6x+30+1
We add all the numbers together, and all the variables
6x+31
Back to the equation:
-(6x+31)
We get rid of parentheses
3x-6x-31+24=0
We add all the numbers together, and all the variables
-3x-7=0
We move all terms containing x to the left, all other terms to the right
-3x=7
x=7/-3
x=-2+1/3

See similar equations:

| 1/2m-0.25=2.75 | | -1x-2(-4x+1)=-16 | | 6(2x+7)=138 | | 3(x-5)^2+11=38 | | 2/5k+0.6=3.6 | | 2x+60=80 | | 12y-3=10y+.5 | | 2/3h-0.25=5.8 | | 5(6x-4)=3(10x+5) | | 10+10x2=x | | 15m^2+8m+1=0 | | 13r+6.72=-13.7r | | 2/5y+0.5=5.5 | | 2/5y+0.5=0.5 | | 12y-3=10y+(1/2) | | 2(-5+5x)=-10 | | 8x-23=15 | | 9p^2+19p+2=0 | | 1.2k+2.3=0.5k7.9 | | X+4(x-2=-12+5x | | 6x-20+2=x | | 50n=46(n+3)-88 | | 6x-20+26x=x | | 4^2+3^2=x^2 | | -14n+2=-7 | | X+4(x-2=-12+5 | | 5.7+y=10.2 | | 90=x+2x+x+10 | | 2/3(b+6)=2 | | 4u-7=-2u | | -31-7x=7(-x-5) | | x+3.5=7.2 |

Equations solver categories